2021
DOI: 10.1088/1402-4896/ac198b
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gamma-ray irradiation on temperature-sensitive electrical characteristics of Graphene/Al2O3/p-type Si structure

Abstract: In this work, the impact of gamma-ray irradiation (γ) on graphene/Al 2 O 3 /p-type Si structure has been investigated. For this, temperature-sensitive current-voltage (I-V ) analyses of the structure exposed to gamma radiation have been carried out. I-V measurements have been made between −3 V and 3 V to analyze electrical properties of the graphene/Al 2 O 3 /p-type Si before and after 60 Co γirradiation. I-V measurements of the structure have been made at the range of 300 K-405 K. Thermionic emission (TE) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The obtained results showed that conductance and capacitance values were increased after γ-ray irradiation and, were decreased when the radiation dose was increased from 30 kGy to 60 kGy [53]. It was shown that 60 Co γ-irradiation had a role play in temperature-sensitive I-V characteristics of Gr-based Schottky structure and increased the generation of free carriers [54].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The obtained results showed that conductance and capacitance values were increased after γ-ray irradiation and, were decreased when the radiation dose was increased from 30 kGy to 60 kGy [53]. It was shown that 60 Co γ-irradiation had a role play in temperature-sensitive I-V characteristics of Gr-based Schottky structure and increased the generation of free carriers [54].…”
Section: Introductionmentioning
confidence: 93%
“…In the obtained results, it was shown that the interface states contributed to the dielectric properties of the structure. We also studied the γ-ray irradiation effect on electrical properties, conductance, and capacitance features of Gr-based Schottky diode with an insulator layer [53,54]. The obtained results showed that conductance and capacitance values were increased after γ-ray irradiation and, were decreased when the radiation dose was increased from 30 kGy to 60 kGy [53].…”
Section: Introductionmentioning
confidence: 98%